The influence of competence on work engagement through the mediation of self-efficacy (A study on Muslim teachers) - Anggraini, Maria; Lubis, Rahmi; Effendy, Sjahril (INSPIRA: Indonesian Journal of Psychological Research, 2024)
This study aims to investigate the influence of competency on work engagement, with self-efficacy serving as a mediating variable, among Muslim teachers in Tanjung Morawa. The study's population comprised 230 teachers. A total sampling technique was employed, resulting in a sample size of 230 individuals. The research adopted a quantitative methodology, utilizing the Competency Scale, Work Engagement Scale, and Self-Efficacy Mediation Scale as measurement instruments. Data analysis was conducted using multiple linear regression tests. The findings of this study indicate that self-efficacy (Z) significantly mediates the relationship between competency and work engagement. These results underscore the importance of competency and self-efficacy in enhancing teachers' work engagement. Therefore, efforts to improve teachers' competency and self-efficacy can be considered effective strategies for increasing work engagement. The implications of this study also provide training programs and interventions that are more focused on enhancing competency and self-efficacy in the workplace context